2020
DOI: 10.1016/j.toxrep.2020.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological and genotoxic evaluation of anacardic acid loaded-zein nanoparticles in mice

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…In our ndings, the stomach weight of the AaZNp increased in comparison to the negative and standard control groups. A similar result was also observed when a short-term subacute toxicity protocol testing the same nanoformulation was analyzed (Araújo et al 2020). Harlita et al (2016) reported that the mean mass of the stomachs did not exhibit any signi cant increase or decrease.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our ndings, the stomach weight of the AaZNp increased in comparison to the negative and standard control groups. A similar result was also observed when a short-term subacute toxicity protocol testing the same nanoformulation was analyzed (Araújo et al 2020). Harlita et al (2016) reported that the mean mass of the stomachs did not exhibit any signi cant increase or decrease.…”
Section: Discussionsupporting
confidence: 75%
“…Although Anacardium occidentale and its phytochemicals are broadly used, few studies access their toxicity, limiting their extensive use (Carvalho et al 2011;Anand et al 2015). A short-term genotoxicity and toxicity assessment was previously performed (Araújo et al 2020). Nonetheless, a subacute topic and systemic toxicity evaluation are mandatory to support its clinical usage, expanding the potential applications of zein nanoparticles containing anacardic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Cashew nut ( Anacardium occidentale L.) is described by Merian as a vermifuge. Components extracted from the nut, such as anacardic acid, have an anti- Trypanosoma cruzi effect [ 136 , 137 ], as well actions against echinococcosis [ 138 , 176 ] and a larvicidal and antimicrobial effect [ 177 ]. The ethanolic extract of the bark of this plant showed an in vitro anthelmintic effect against the parasite Onchocerca ochengi [ 176 ].…”
Section: Resultsmentioning
confidence: 99%
“…AA and its derivatives are well-known for their therapeutic applications ranging from antitumor, antibacterial, antioxidant, anticancer, and so forth [ 32 ]. Many studies have shown that AA has no serious toxic and side effects in a certain concentration range [ 33 , 34 ]. Thus, the findings of this study can provide a new candidate drug for the prevention and treatment pathological cardiac hypertrophy caused by neurohumoral factor disorder in clinical.…”
Section: Discussionmentioning
confidence: 99%